The role of inflammation and allergy in acute coronary syndromes - ÖZBEN SADIÇ, BESTE; ERDOĞAN, OKAN (My University, 2008)
It is well known that inflammatory mechanisms play a crucial role in the pathogenesis of atherosclerosis and coronary artery disease. In recent years, allergic episodes have been shown to be associated with acute coronary syndromes. Mast cells release certain inflammatory mediators including histamine and neutral proteases during an allergic episode and these inflammatory mediators are implied to induce coronary artery spasm and/or atheromatous plaque erosion or rupture. As the inflammatory component of acute coronary syndromes is a potential therapeutic target, drugs that stabilize mast cell membrane and monoclonal antibodies that protect mast cell surface may be effective in preventing allergy associated acute coronary syndromes. In this review, we will mention the role of inflammation and allergy and anti-inflammatory therapeutic modalities in acute coronary syndromes. © 2008 Bentham Science Publishers Ltd.
Keywords: Acute coronary syndromes (ACS); Allergy; Coronary artery disease; Inflammation; Inflammatory mediators; Mast cell; Pathogenesis